Geolinguistic patterns of diffusion in a Spanish Region: The case of the dialect of Murcia - Hernández-Campoy, Juan Manuel (Sociolinguistic Studies, 2003)
A paradigm whose existence is older than that of the covariation of linguistic and social phenomena is the possible relationship between the regional transmission of linguistic phenomena and geographical factors. Nevertheless, its systematic observation and the application of models from human geography is rather recent and sporadic. In the same way as the Region of Murcia has historically been a transition area of South-eastern Spain where many different cultures and civilizations have met, the Spanish spoken in Murcia is a transition variety, sharing features with Valencian Catalan, Castilian, Aragonese and Andalusian Spanish, and having a traditional characterisation as an eminently non-standard speaking region. With all this in mind, the aim of this article is to show and analyse the relationship between the geolinguistic patterns of diffusion of the standard Castilian Spanish over the Murcian territory and the (increasingly) actual use of standard forms in these traditionally non-standard areas. The real presence or absence of some degree of standardisation as well as its intra-regional variation will reveal to us whether the detected geolinguistic patterns of linguistic uniformisation are applicable to the Region of Murcia.